(untitled) (Indian Journal of Arid Horticulture, 2025)
Tomato plays an important role in supplementing the income of small and marginal farmers of major area of the India. The main constraints of low quality and productivity of this vegetable in arid region of Rajasthan (India) may be due to partial adoption of improved production technology practices by the tomato growers. The present study was undertaken by ICAR-CAZRI, Krishi Vigyan Kendra, Pali-Marwar (Rajasthan) to address the yield gap through Front Line Demonstrations (FLDs) on tomato crop during three different years (2019-20, 2022-23 and 2023-24) at three selected villages (total 45 demonstrations) of the Pali district. Prevailing farmer’s practices were treated as control for comparison with recommended practices. In the three years data it was observed that improved practices helped in managed the incidence of pest and diseases, increased productivity and quality of the produced. Due to this an average yield of 429.17 q/ha was obtained in demonstrated plot over control (364.23 q/ha) with an additional yield of 64.94 q/ha and the increasing the average tomato productivity by 17.75 per cent. The average extension gap and technology gap ware 64.94 q/ha and 320.83 q/ha, respectively, with the average technology index of 42.77 per cent during the demonstration years. Besides this, the demonstrated plots gave higher gross return (Rs. 5,31,871), net return (Rs. 3,60,704) with higher benefit cost ratio (3.08) when compared to farmer’s practice. The performance of demonstrated package of practices even though after FLD programme, which shows positive impact of FLD on adoption of demonstrated production technology.